Pengaruh Model Pembelajaran dan Kemampuan Berpikir Kreatif Terhadap Hasil Belajar Sejarah Peserta Didik di SMA Negeri 30 Jakarta - Nur Indah Lestari (Jurnal Pendidikan Sejarah, 2016)
This research aims to investigate the influence of instructional models and creative thinking ability toward history learning outcomes of students at SMA Negeri 30 Jakarta. This research is quantitative research using design treatment by level 2x2. The instrument used to assess student’s achievement is in the multiple choice form, while the instrumen used to assess students creative thinking’s ability is in questionnaire form. The result of the research show that: history learning outcomes of students using sinektik learning models are higher than those history learning outcomes of students using cooperative learning tipe group investigation models, here is interaction effect between learning model and creative thinking on history learning outcomes of students, history learning outcomes of students who has high creative thinking and using sinektik learning model are higher than students using cooperative learning tipe grup investigation model, history learning outcomes of students who has creative thinking and using sinektik model are lower than students using the cooperative learning tipe grup investigation models.